Analisis kinerja keuangan BPD DIY dan BPD BJB menggunakan analisis likuiditas, profitabilitas, dan solvabilitas - Valenty, Yola Andesta; Santoso, Fahrul Imam (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study describes the Financial Performance Analysis of PT Bank BPD DIY and PT BPD Jawa Barat and Banten Tbk by comparing financial performance in financial statements using analysis of liquidity ratios, profitability ratios, and solvency ratios in the 2016-2018 period. Both are companies owned by Regional Owned Enterprises (BUMD). PT Bank BPD DIY is a BUMD managed privately in its capital and share ownership, in contrast to PT BPD Jawa Barat and Banten Tbk, which have